Hydrodynamic and Hydromagnetic Stability of Viscous-Viscoelastic Superposed Fluids in Presence of Suspended Particles. (27th June 2007) - Kumar, Pardeep; Singh, Mahinder
Abstract : The Rayleigh‐Taylor instability of a Newtonian viscous fluid overlying an Oldroydian viscoelastic fluid containing suspended particles is considered. As in both Newtonian viscous-viscous fluids, the system is stable in the potentially stable case and unstable in the potentially unstable case, this holds for the present problem also. The effect of a variable horizontal magnetic field is also considered. The presence of magnetic field stabilizes a certain wavenumber band, whereas the system is unstable for all wavenumbers in the absence of the magnetic field for the potentially unstable arrangement.